Setting up and operationalizing a health professions education research (HPER) unit: AMEE guide no.170 - Kitto, Simon (2024)
In the same way as clinical medicine, health professions education should be evidence-based rather than based on tradition and convenience. Health professions education research (HPER), an academic area that first emerged in the 1950s, is essential for identifying new and better ways to educate health professionals. Again, just as with clinical research, setting up sustainable HPER units is critical to coordinate research efforts and facilitate the production of clear and strategic HPER. In this AMEE guide we draw upon the scholarly and grey literature and our own experiences as HPER unit leaders in several different global contexts to provide practical guidance on establishing and sustaining a HPER unit. We outline the multiple elements and considerations required to set up and operationalize a successful HPER unit, from engagement of key stakeholders and documentation of milestones to the production of programmatic research and its implementation. These are considered under the areas of  • Who do you need to partner with?  • Setting the agenda - or What will your unit be known for?  • Your most valuable resource - people!  • Operationalizing your HPER agenda  • Leading the way   We provide concrete tips on each of the above and illustrate these key steps with examples from our own experiences or the wider literature. Whether the reader is beginning, maintaining, or seeking to renew their HPER unit, we hope that the guidance we provide is as useful as it has been to us during our own research program building endeavours.